EXAMINATION OF RELATIONSHIP BETWEEN 30 SECOND WINGATE TEST PERFORMANCE AND SPIROMETRIC RESPIRATORY FUNCTIONS IN YOUNG ADULTS - Arslan, C.; Koz, M.; Guer, E.; Karadag, A. (Inst Sport, 2009)
Objective: This work has been planed to investigate whether the correlation between one of the important component of the sports performance spirometric respiratory function (SRF) and 30 s Wingate Test (WT) parameters of young adults who have different physical fitness level. Materials and Methods: This work included a total of 166 subjects those are 98 young boys (20.30 +/- 1.93) and 68 young girls (19.65 +/- 2.18). The subjects were divided into two groups namely regular exercises group (EG) who make a regular exercises during 4.0 +/- 1.50 years and sedentary groups (SG). Both group's subjects have similar age, height, weight and body mass index (BMI kg/m(2)). All the subjects were performed spirometric respiratory function test and WT power performance test. Statistical analyses were performed by SPSS computer program and the groups were compared to each other by using Independent Samples t test calculation and the correlation relation levels were calculated by using linear regression analysis. Results: In the view of physical peculiarities, it has not been found any difference between research groups that EG and SG (P>0.05). In the meaning of the measured spirometric respiratory functions and WT power performance, with the advantage of making regular sports, according to SG groups, the boys and girls EG groups showed differences (P<0.05). The correlational relationship between the spirometric and WT power parameters; it has been observed significant correlation between peak power (PP), mean power (MP), peak power/weight (PP/W-kg, mean power/weight (MP/W-kg) form WT parameters and VC, FVC, FEV1, FEV1/FVC (%), FEF25-75, PEF and MVV form respiration function (P<0.05 and P<0.001). On the other hand, it has not been found any significant correlation between WT anaerobic fatigue index (AFI %) and respiratory functions (P<0.05). Conclusion: In this work, the tested spirometric respiratory functions have got an active role in the WT power parameters. It has been confirmed that there is a positive tendency significant higher correlation between VC, FVC, FEV1, FEV1/FVC (%), FEF25-75, PEF, MVV and WT parameters in both antrene and non-antrene groups.
10th ICHPER-SD Europe Congress/TSSA 8th International Sports Sciences Congress -- NOV 17-20, 2004 -- Antalya, TURKEY
Keywords: Spirometry; Respiratory functions; Exercise; Wingate test